HUMOR AND SPORTS PERFORMANCE IN PRACTITIONERS OF AMATEUR FOOTBALL (Fiep Bulletin - online, 2016)
The aim of this study was to evaluate the moods of amateur footballers. For the research were asked 30 males aged above 40 years, playing amateur football for more than two years in the city of Patos, Paraiba. For data collection was used questionnaire POMS (mood state profile), which contains 42 items, which address the force as a positive factor of humor and as negative factors presents: anger, fatigue, mental confusion, tension, depression. The data were answered on the questionnaire POMS, marking an "X", in which the mood which is the individual, the terms being used for evaluation at all, a little, moderately, and quite a lot. Then it was made the statistical analysis to develop the search result. As a result of the questionnaire, it was analyzed that the levels of force of amateur soccer players had a significant result, thereby contributing to the affirmation that individuals have a positive mood for the amateur football. And the negative factors, stress, anger, depression, mental confusion and fatigue did not show significant results, thus concluding that the moods of the players of amateur football research participants are influenced by the practice of football.
Keywords: Amateur football; sports performance; Humor.